Indian Himalayan Arabidopsis thaliana population reflects deep history and might be the source of species expansion in the eastern edge - Akanksha Singh; Ashwani Kumar Verma; Abhinandan Mani Tripathi; Parneeta Mishra; Sumit Kumar Bag; Sivasubramanian Rajarammohan; Sribash Roy (BMC Plant Biology)
Abstract Deciphering the origin, demography and adaptation strategies of species are important goals of biologists. In this context, the model plant species Arabidopsis thaliana has been studied in details using regional and large scale global collections. However, these studies did not include Indian Himalayan populations. This might have restricted our current knowledge on the species. To understand the species evolution and demography in global scale vis-à-vis unexplored Indian Himalayan populations, we analysed 38 whole genome sequences of A. thaliana those are originated along a steep elevation gradient in the Himalayas along with the available largest global collections so far. Whole genome sequence analyses indicated existence four distinct sub-populations at different elevations in Indian Himalayan region. Unexpectedly, we observed the Indian population is more diverse than Eurasian populations and more importantly comparable with the known most diverse ancestor populations, the relicts. The genetic diversity of Indian populations was found to decrease towards east and west of its peripheral region. It might have evolved in the region without genomic admixture with Eurasian non-relicts, harbour large number of unique alleles, rare S-haplogroups with high frequency and without any recombinant S-haplogroup types. Like the relicts, Indian population follows geographic scales strong isolation by distance patterns. Along with our own findings and earlier observations we show that while one sub-population of African ancestors swept the most of the Euro-Asian regions, another one migrated towards east that contributed in the expansion of the species in its peripheral region particularly towards east. Our results add to the existing knowledge on the species demographic history across the globe. Background Arabidopsis thaliana has been extensively studied as a model species for understanding its origin, demography, population genetics, and epigenetics at regional and global scales. Comprehensive global studies, such as the 1001 Genomes Project, revealed that present-day A. thaliana originated from multiple glacial refugia, with non-relict populations widely expanding across geographic regions, though their origin in the Balkans and Black Sea areas and subsequent expansion to the Far East remain debated due to climatic variability. The Himalayan region presents a unique phyto-geography with diverse climatic conditions, ranging from subtropical to alpine, providing a biodiversity hotspot for diversification and speciation. However, global studies have largely excluded this region. This study analyzed 38 A. thaliana genomes from eight West-Himalayan populations in the context of global datasets to investigate the diversity, origin, and evolutionary history of these populations. The primary objectives were to explore the role of the Himalayan populations in global diversity and their potential contribution to the east–west expansion of A. thaliana, considering the region’s vast climatic gradients. Result The analysis of 38 whole-genome sequences of Arabidopsis thaliana from the Indian Himalayas revealed four distinct sub-populations distributed along an elevation gradient. Indian populations exhibited higher genetic diversity than Eurasian populations, comparable to relict populations, and harbored unique alleles, rare S-haplogroups, and no recombinant S-haplogroups. Diversity decreased towards the east and west of the region, suggesting independent evolution without admixture from Eurasian non-relicts. Isolation-by-distance patterns were observed, similar to relicts. These findings indicate that Indian populations likely contributed to the species’ eastward expansion and provide new insights into the global demographic history of A. thaliana. Conclusion Indian Himalayan populations of Arabidopsis thaliana exhibit high genetic diversity, comparable to relict populations, and likely evolved independently without admixture from Eurasian non-relicts. These findings highlight their significant role in the species’ eastward expansion and global demographic history.